2020
DOI: 10.3390/molecules25235737
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MCFA and Other Methods of Terminating Alcohol Fermentation and Their Influence on the Content of Carbonyl Compounds in Wine

Abstract: This study deals with the effects of the use of a mixture of medium-chain fatty acids (MCFA) at the end of the alcohol fermentation process on the content of carbonyl compounds in wine. During the experiment, the effects of the addition of MCFA at doses of 10 and 20 mg/L were compared to the termination of alcohol fermentation using cross-flow filtration and chilling treatments. Individual carbonyl compounds were determined by HPLC analysis. The experiment showed that the addition of MCFA caused a reduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…The results confirm the fact that MCFA is a significant inhibitor of alcoholic fermentation [3,9,12]. At the same time, the hypothesis was confirmed that with the help of MCFA, it is possible to terminate alcoholic fermentation even at lower doses of SO 2 [22,30]. inhibitor of alcoholic fermentation [3,9,12].…”
Section: Glucose + Fructosesupporting
confidence: 80%
See 2 more Smart Citations
“…The results confirm the fact that MCFA is a significant inhibitor of alcoholic fermentation [3,9,12]. At the same time, the hypothesis was confirmed that with the help of MCFA, it is possible to terminate alcoholic fermentation even at lower doses of SO 2 [22,30]. inhibitor of alcoholic fermentation [3,9,12].…”
Section: Glucose + Fructosesupporting
confidence: 80%
“…inhibitor of alcoholic fermentation [3,9,12]. At the same time, the hypothesis was con firmed that with the help of MCFA, it is possible to terminate alcoholic fermentation even at lower doses of SO2 [22,30].…”
Section: Glucose + Fructosementioning
confidence: 99%
See 1 more Smart Citation
“…According to our experiences, the concentrations of caproic acid, caprylic acid, and capric acid in reductive white wines of best quality are under 5 mg L À1 , at least under 10 mg L À1 . These acids in combination, above 10 mg L À1 concentration have significant inhibitory effect on yeasts that may lead to stuck fermentation (Baron et al, 2017;Licek et al, 2020). The concentrations of MCFA ethyl esters in quality white wines should be under 20 mg L À1 according to our experiences.…”
Section: Alcoholic Fermentation Applying Nitrogen Supplementsmentioning
confidence: 90%
“…The inhibiting effect of MCFAs on yeasts was thoroughly investigated, 10 mg L À1 dose of MCFA mixture had a toxic effect on Saccharomyces cerevisiae (Baro n et al, 2017). The effect of a mixture of MCFA at the end of the alcoholic fermentation process on the content of carbonyl compounds in wine was also investigated (Licek et al, 2020). During the production of red wines (Carmenere), authors observed the increased formation of MCFAs at elevated temperatures, therefore they suggest to keep temperature under 28 8C (Restrepo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%